THE EFFECT OF DISCLOSURE OF SUSTAINABILITY REPORTING BASED ON GRI STANDARDS ON COMPANY PERFORMANCE (Study on Non-Financial Companies Listed on the SRI-KEHATI Index 2017-2019) - Yuyun Eriyanti (Jurnal Akuntansi Trisakti, 2022)
This research was conducted to test: (1) The effect of the economic dimension sustainability report disclosure on company performance; (2) The effect of the environmental dimension sustainability report disclosure on company performance; (3) The effect of disclosure of the social dimension sustainability report on company performance. The population of this study was 30 companies listed on the SRI-KEHATI index 2017-2019. Based on the purposive sampling method, the total sample of the study was 14 companies. Hypothesis testing is carried out in this study using multiple linear regression analysis with the help of SPSS version 26 software. The results showed that (1) the economic dimension has no effect on company performance (Tobin's Q) with a significance level of the economic dimension of 0.450. (2) The environmental dimension has an effect on company performance (Tobin's Q) with a significant level of the environmental dimension of 0.002. (3) The social dimension affects Company Performance (Tobin's Q) with a social dimension significance level of 0.000.